Shaping a Generation of Young Leaders Based on Quality Education with LDKS Activities in Asriloka Wonosalam Ecotourism Area - Nuryadi; Pratama, Devangga Putra Adhitya; Anindiyadewi, Nabila Carissa (CV. Science Tech Group, 2025)
This study aims to analyze the role of Quality Education in forming a generation of young leaders through Basic Student Leadership Training (LDKS) implemented in the Asriloka Wonosalam Ecotourism Area. Using the Systematic Literature Review (SLR) method with a comparative qualitative descriptive approach, this research examines various literatures related to leadership education, ecotourism, and sustainable development. The results show that the integration of the Quality Education concept in ecotourism-based LDKS contributes significantly to building adaptive, innovative and sustainability-oriented leadership characters. LDKS participants gain direct leadership experience through experiential learning, which includes managerial skills, decision making, problem solving, and social and environmental awareness. In addition, the ecotourism area provides a supportive learning environment, where participants can develop conservation-based leadership skills, green entrepreneurship, and community empowerment. The implication of this study confirms that the ecotourism-based LDKS approach can be an effective alternative education model in producing young leaders who are not only smart and competitive, but also have high concern for the environment and society. Therefore, it is necessary to strengthen the curriculum, increase collaboration between educational institutions, ecotourism managers, and local communities, as well as continuous evaluation to ensure the effectiveness of the program in the long term.